Global status report on noncommunicable diseases 2010 - Alwan, Ala (World Health Organization GenevaCH, 2011)
Presents statistics, evidence and experiences. Uses global, regional and country-specific data to document the magnitude of the problem, projects future trends, and assesses the factors contributing to these trends.